2004
DOI: 10.1186/1477-7525-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundThe purpose of this report is to examine the correlates of quality of life (QOL) of a well-defined group of long-term breast cancer survivors diagnosed between the ages of 40 and 49.MethodsWomen were eligible if they were diagnosed with invasive breast cancer or ductal carcinoma in situ 5 to 10 years before June 30, 1998 and were enrolled at Group Health Cooperative, a health maintenance organization in western Washington State. A questionnaire was mailed to 290 women; 216 were included in this analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 19 publications
6
24
0
Order By: Relevance
“…Results from studies examining HRQOL in breast cancer survivors appear to have similar findings [35]. In fact, the mental HRQOL in our study was better than the mean MCS scores of breast cancer survivors who were on average seven years post-diagnosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results from studies examining HRQOL in breast cancer survivors appear to have similar findings [35]. In fact, the mental HRQOL in our study was better than the mean MCS scores of breast cancer survivors who were on average seven years post-diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, the mental HRQOL in our study was better than the mean MCS scores of breast cancer survivors who were on average seven years post-diagnosis. The PCS values for the breast cancer survivors that had received chemotherapy were similar to the ovarian cancer survivors in our study, while breast cancer survivors who received hormonal therapy only or no systemic therapy had higher PCS than our study population [35]. …”
Section: Discussionmentioning
confidence: 52%
“…Chemotherapy also has been reported to predict impaired QOL in 5- and 10-year survivors. 51,52 QOL following specific adjuvant treatment regimens has been described in longitudinal studies with patients receiving radiation, 44,45,53 chemotherapy, 54 radiation and chemotherapy, 55,56 and endocrine therapy. 5760 However, unlike these studies, we included an adjuvant chemotherapy*time interaction term in our analysis—in relation to receipt of BCS or mastectomy as well—allowing us to determine if, and how, the change in QOL over time differed by receipt of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous reports on depression and its correlates, the relation between sociodemographic and clinical factors and depression after diagnosis of breast cancer remain controversial [1, 2, 1315, 17]. It has been suggested that sociodemographic factors, such as age, marital status, and socioeconomic status are associated with depression [1, 2, 14, 15, 17–19].…”
Section: Introductionmentioning
confidence: 99%